Financial Reporting Classism Based on Karl Marx’s Theory of Classes - Bernadetha Athalia; Tjiptohadi Sawarjuwono (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2015)
This research aims to classify the companies’ annual reports into the classes based on Theory of Classes and to analyze the classism behavior through narrative analysis. The different interests among the readers create a classism practice that can be classified into two classes of rea-ders based on Theory of Classes: Bourgeoisie and Proletariat. Narrative analysis method is used to reveal the hidden meanings behind some sentences in annual reports. This research claims that annual reports of PT Telekomunikasi Indonesia, Tbk (Telkom) and PT Perusahaan Gas Negara, Tbk (PGN) give more information to shareholders and govern-ment, it means these annual report reflect bourgeoisie class.They pro-vide so many persuasive sentences in their annual reports in order to get legitimacy from their shareholders, but they do not give detailed infor-mation to their employees as a proletariat class.